Structural brain imaging abnormalities correlate with positive symptom in schizophrenia. (21st June 2022) - Zhang, Meng; Xiang, Hong; Yang, Fude; Fan, Hongzhen; Fan, Fengmei; Song, Jiaqi; Wang, Zhiren; Tan, Yunlong; Tang, Shiyou; Tan, Shuping; Elliot Hong, L.
Highlights: It is the first study to systematically investigate structural changes in patients with FES using a new toolbox, CAT12. Reduced grey matter volume in the right superior temporal gyrus was found in patients with FES compared with healthy controls (HCs). Cortical thickening in the insula was found in patients with FES compared with HCs. Altered neuroanatomical changes are related to positive symptoms in patients with FES. Abstract: Accumulating evidence indicates neuroanatomical mechanisms underlying positive symptoms in schizophrenia; however, the exact structural determinants of positive symptoms remain unclear. This study aimed to investigate associations between positive symptoms and structural brain changes, including alterations in grey matter (GM) volume and cortical thickness, in patients with first-episode schizophrenia (FES). This study included 44 patients with FES and 48 healthy controls (HCs). Clinical symptoms of patients were evaluated and individual-level GM volume and cortical thickness were assessed. Patients with FES showed reduced GM volume in the right superior temporal gyrus (STG) and increased cortical thickness in the left inferior segment of the circular sulcus of the insula (S_circular_insula_inf) compared with HCs. Increased thickness of the left S_circular_insula_inf correlated positively with positive symptoms in patients with FES. Exploratory correlation analysis found that increased thickness of the left S_circular_insula_inf correlated positively with conceptual disorganization and excitement symptoms, and the right STG GM volume correlated negatively with hallucinations. This study suggests that GM abnormalities in the STG and altered cortical thickness of the S_circular_insula_inf, which were detected at the early stage of schizophrenia, may underlie positive symptoms in patients with FES.